Trends in prevalence of hearing loss in adults in the USA 1999-2018: a cross-sectional study - Fengxin Mo; Shiheng Zhu; Hanlu Jia; Yuan Xia; Li Lang; Qiutong Zheng; Xiaojing Yuan; Shan Wu; Yan Bai; Wenhan Yang; Liang Wang; Qingsong Chen (BMC, 2024)
Abstract Background A better understanding of how the prevalence of hearing loss and its associated factors change over time could help in developing an appropriate program to prevent the development of hearing loss. Methods Population-representative cross-sectional data from the United States National Health and Nutrition Examination Survey (NHANES) were used to estimate the trends in the prevalence of hearing loss among adults in the USA over the period 1999-2018. A total of 15,498 adult participants aged 20 years or older had complete audiometric examination data. Logistic regression was employed to evaluate the trend in hearing loss; weighted Rao-Scott χ2 tests and univariate logistic regression analyses were used to examine the association between hearing loss and relevant factors. Results The overall hearing loss prevalence in 1999-2018 was 19.1% 19.1 (95% CI, 18.0-20.2%). The prevalence of hearing loss decreased in cycles (P for trend < 0.001). For participants aged 20-69 years, the prevalence decreased from 15.6% (95% CI, 12.9-18.4%) in 1999-2000 to 14.9% (95% CI, 13.2- 16.6%) in 2015-2016; for participants aged > 70 years the prevalence decreased from 79.9% (95% CI, 76.1-83.8%) in 2005-2006 to 64.5% (95% CI, 58.8-70.2%) in 2017-2018. Participants with hearing loss were likely to be older, male, non-Hispanic white, and to have not completed high school. Mild hearing loss was more prevalent among those aged 20-79 years; in those aged over 80 years the prevalence of moderate hearing loss exceeded that of mild loss. Among all otologically normal participants, hearing thresholds increased with age across the entire frequency range. Conclusions The prevalence of hearing loss in USA adults changed over the period 1999-2018. The trends observed provide valuable insight for making public health plans and allocating resources to hearing care. Further investigation is necessary to monitor hearing loss and its potential risk factors.